Thermoelectric properties of silicides with topologically non-trivial electronic structure: Co1-xMxSi (M=Fe, Ni). (2019) - Burkov, A.T.; Ivanov, Yu.V.; K.Nielsch,; Novikov, S.V.; Perez, N.R.; Pshenay-Severin, D.A.; Reith, H.; Schnatmann, L.U.; Schierning, G.; Volkov, M.P.
Abstract: We present experimental and theoretical results on electronic structure and thermoelectric properties (electrical resistivity and Seebeck coefficient) of Co1−x Mx Si (M=Fe, Ni) compounds. Cobalt monosilicide, CoSi, is a recent candidate to the family of materials with topologically non-trivial electronic structure. Moreover, the compound has been considered as a promising thermoelectric material. According to literature data the maximum experimental thermoelectric efficiency parameter ZT of CoSi is close to 0.2. The combination of the unique electronic structure, promising thermoelectric properties and phase stability in a broad temperature range makes CoSi suitable to study the effect of topological states, both bulk and surface (Fermi arcs), on thermoelectric properties. We measured thermoelectric properties (Seebeck coefficient and electrical resistivity) of Co1−x Mx Si from 4 K to 800 K. Electronic structure of the compounds was calculated using density functional theory as implemented in VASP software package. Possible connections of the observed peculiarities in the thermoelectric properties with topological features in the electronic structure of the compounds are discussed